THE INFLUENCE OF CAREER DEVELOPMENT AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) ON TURNOVER INTENTION THROUGH AFFECTIVE COMMITMENT - Suryatunnisak, Suryatunnisak; Handoyo, Leonardus Teguh; Arfi, Lingga Ramadhana (Penelitian dan Pengembangan Ilmu, 2025)
In this study, the aim is to analyzeThe Influence of Career Development and Organizational Citizenship Behavior (OCB) onTurnover Intention Through Affective CommitmentThis research was conducted at PT. Brataco Pekanbaru. The data source for this research was from employees of PT. Brataco Pekanbaru, Riau, Indonesia. The sample size was 30 respondents. Furthermore, the data analysis techniques were descriptive analysis, convergent and discriminant validity tests, reliability tests, and SEM-PLS analysis. The results of the research: from the processed data. Shows the calculation of the influence of variables Career Development has a significant influence on Affective Commitment, Organizational Citizenship Behavior to Affective Commitment does not have a significant effect,Affective Commitment has a direct impact onTurnover Intention, career development to Turnover Intention through Affective Commitment significantly influence Organizational Citizenship Behavior on Turnover Intention through Affective Commitment There is no significant influence.